Bioactive compounds and antioxidant activity of Feijoa (Feijoa sellowiana berg) cultivated in subtropical zones of Georgia - Baratashvili, Davit; Vanidze, Maria; Kedelidze, Nino; Kalandia, Aleko; Djafaridze, Indira; Lomtatidze, Nino; Nakashidze, Irina; Ceccarini, Maria Rachele; Beccari, Tommaso (Progress in Nutrition, 2022)
Feijoa is one of the most interesting fruit cultures in Georgia. Feijoa is a cross-pollinated plant. Therefore, it produces huge variety from selectionist point of view. New forms differ not only in their structure but also in chemical composition. 10 samples of Feijoa were chosen from different regions of Georgia and their chemical characteristics were determined. Moreover, DPPH method was used for determining their antioxidant activity. Our investigation has revealed that out of ten samples four were the most interesting for their chemical properties such as the amount of total phenols, Flavonoids, Catechins and antioxidant activity.